An outreaching model of tertiary difficult asthma care reduces adverse asthma outcomes and healthcare utilisation costs. Issue 6 (23rd March 2016) - Patil, Veeresh K.; Townshend, Christine; Mitchell, Frances; Kurukulaaratchy, Ramesh J.
Difficult asthma is a heterogeneous state, pragmatically defined by the British Thoracic Society (BTS) as "persistent symptoms and/or frequent exacerbations despite treatment at step 4 or step 5 treatment" [1, 2]. It is frequently associated with aggravating comorbidities, causes significant morbidity and healthcare costs, and requires rigorous systematic assessment and treatment approaches [3–7]. Though few exist, referral to a specialist centre with appropriate multidisciplinary expertise and supporting technical resource is recommended [8]. It is unclear whether such care can be effectively delivered in a peripheral healthcare setting. We report initial outcomes of such a care pathway on the Isle of Wight (IOW), UK. Outreaching specialist asthma care can significantly benefit patients with difficult asthma in peripheral settings http://ow.ly/YClKM